Development of Oil Vehicle Screening Method for Bromo Acid Dye-Based Color-Changing Cosmetic Formulation - Susanto, Eriwan; Cita, Juang Arwafa; Sujilah, Ajeng Rana Wulan; Satrialdi, Satrialdi; Suciati, Tri; Nugraha, Yuda Prasetya (Fakultas Farmasi Universitas Andalas, 2024)
Bromo acid dye (Red 21) recently gained attention in the production of color-changing cosmetics. The critical aspect in the development of cosmetic products using this dye group is the compatibility of its oil vehicles. The compatibility of bromo acid dyes with oil vehicles is determined by several parameters such as the dye solubility in the oils, clarity of the mixture, and the ability to change color when the pH of the solution is adjusted to match the skin’s pH. Therefore, this study conducted the compatibility study by examining the ability of 27 oil samples to dissolve Red 21. The ability of a vehicle to dissolve a compound is influenced by the polarity of the vehicle. Hence, a correlation was established between the relative polarity of oils and their ability to dissolve Red 21. The results showed that the water-oil interfacial tension was negatively correlated (r = -0.64) with Red 21 solubility in the oil. From this research, the water-oil interfacial tension represented the relative polarity of the oil and was considered sufficient to predict the compatibility of the oil with Red 21. In addition, hydrocarbon and silicone oils are not compatible with Red 21.